Students’ social presence in online learning - Jamil, Nur Jannah (2014)
The purpose of this study is to identify students’ perceptions on social presence on online learning and to investigate students’ actual social presence in online learning. Next, this study will also analyze the relationship of students’ actual social presences perceived by students with students’ perceptions on social presence and also its relationship with their academic performance. This study was carried out with 30 undergraduate students who enrolled in Authoring Language course. This study implemented quantitative approach with triangulation of data from questionnaire and students’ online transcript in e-learning forum. Quantitative data from questionnaires were analyzed using Statistical Package for the Social Science (SPSS). As for the online transcript, it was analyzed through content analysis technique. The results of this study show that; social respect and social identity has been identified as the highest perceived social presence in online learning based on the students’ perception, which then followed by open mind, social sharing and intimacy. Besides that, there is insignificant relationship between students’ perceptions on social presence and their actual social presence. On the other hand, in the affective dimension, expression of emotion has been identified to have the most occurrences, while continuing a thread has been recognized as the most responses recorded for interactive dimension and salutation and greetings have been analyzed as the most occurred instances for cohesive dimension. Based on the perception, male students have been identified as perceiving social presence more than female, wherethere is insignificant relationship between gender difference and students’ perception on social presence. However, social presence has significant relationship between both coursework and examination marks. Moreover, students used the responses of interactive dimension the most, cohesive had been averagely used and affective dimension had been recorded as the lowest usage across the entire six weeks of online discussions. In conclusion, by being aware and acknowledge the dimensions, indicators and responses, students and teacher would have higher percentage in making the interaction beneficial for learning.